The Tensile Strength of Loess in Northwest China by Unconfined Penetration Test and the Distinct Element Simulation - Xuyang Wu; Yun Bao; Mingyang Ren; Qingguo Liang (Advances in Civil Engineering)
The unconfined penetration test (UP test) is one of the indirect methods to measure the tensile strength of soils. Through a series of UP tests of undisturbed and remolded loess, the split angle (α) of the wedge body which was shaped in the process of the experiment was discussed. And then, the particle movement, the force transfer, and the fracture development law of the sample were studied by the distinct element method (PFC2D). The experiment and numerical simulation results show the following: (1) the split angle (α) presents an exponential decrease with tensile strength (σt) and a linear decrease with internal friction angle (φ); (2) K that can be written as tan (2α + φ) is a coefficient to calculate tensile strength, which is equal to 2.00 for remolded loess and 1.50 for undisturbed loess; (3) the distinct element simulation shows that the resisting force by the UP test comes from both tensile stress and shear stress; (4) the tensile fractures and shear fractures appear at almost the same time when the tensile stress is approximately 70% of tensile strength.